Linguistic Policy in Yakutia in Context of Soviet Nation-Building of 1920-1930: New Yakut Alphabet - E. P. Antonov; E. N. Romanova (Научный диалог)
The authors present the concept of alphabetical construction in Yakutia during the Soviet modernization. It is emphasized that the Yakut region as a special historical and cultural space was characterized by the intensity of civilizational dialogue and exchange of ideas, political strategies and practices. The authors note that the socialist reconstruction actualized the “linguistic” turn in the intellectual environment of the Yakut ASSR in the 1920s-1930s. Two principal positions are characterized in the ongoing heated debate about the graphics of the Yakut alphabet (Cyrillic, on which N. N. Poppe, E. K. Pekarskiy, A. E. Kulakovskiy and V. N. Leontyev insisted, and Latinized, advocated by A. N. Samoylovich, B. M. Grande, S. A. Novgorodov, P. A. Oyunsky). Special attention is paid to the linguistic project developed by the linguist G. V. Baishev (Altan Saryn), which echoes the ideas of linguistic pan-Turkism. For the first time P. A. Oyunsky’s scientific activity in the years of postgraduate study in Moscow (1932-1935), where he was in the “ideological” circle of outstanding linguists, is analysed. It is shown that the worldview and practice of the national intelligentsia were concentrated on experiments on alphabetical construction. The novelty of the research is seen in the methodological innovation: the combination of approaches of transnational and intellectual history allowed to reveal the importance of the presented language projects in the framework of political discourse.